A comprehensive study evaluating germline FANCG variants in predisposition to breast and ovarian cancer - Soukupova, Jana; Stastna, Barbora; Kanwal, Madiha; Hojny, Jan; Zemankova, Petra; Borecka, Marianna; Cerna, Leona; Cerna, Marta; Cerna, Monika; Curtisova, Vaclava; Dolezalova, Tatana; Duskova, Petra; et al. (Cancer medicine, 2024)
BACKGROUND: Monoallelic germline pathogenic variants (GPVs) in five Fanconi anemia (FA) genes (BRCA1/FANCS, BRCA2/FANCD1, PALB2/FANCN, BRIP1/FANCJ, and RAD51C/FANCO) confer an increased risk of breast (BC) and/or ovarian (OC) cancer, but the role of GPVs in 17 other FA genes remains unclear. METHODS: Here, we investigated the association of germline variants in FANCG/XRCC9 with BC and OC risk. RESULTS: The frequency of truncating GPVs in FANCG did not differ between BC (20/10,204; 0.20%) and OC (8/2966; 0.27%) patients compared to controls (6/3250; 0.18%). In addition, only one out of five tumor samples showed loss-of-heterozygosity of the wild-type FANCG allele. Finally, none of the nine functionally tested rare recurrent missense FANCG variants impaired DNA repair activities (FANCD2 monoubiquitination and FANCD2 foci formation) upon DNA damage, in contrast to all tested FANCG truncations. CONCLUSION: Our study suggests that heterozygous germline FANCG variants are unlikely to contribute to the development of BC or OC.
Keywords: zárodečné mutace; dospělí; oprava DNA; nádory vaječníků; nádory prsu; Germ-Line Mutation; Fanconi Anemia Complementation Group G Protein; Female; Adult; ženské pohlaví; lidé; protein FANCG; Breast Neoplasms; Ovarian Neoplasms; studie případů a kontrol; genetická predispozice k nemoci; DNA Repair; Genetic Predisposition to Disease; Case-Control Studies; Aged; lidé středního věku; senioři; Middle Aged; Humans